Positive electrode material and preparation method thereof, positive electrode plate and lithium ion battery
By covering Bi2SeO5 on the ternary positive electrode material LiNixM1-xO2, a core and shell structure is formed, the problem of reaction between the ternary positive electrode material and the electrolyte is solved, and the stability, safety and rate performance of the lithium-ion battery are improved.
Patent Information
- Application Number
- CN202411494808.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-04
AI Technical Summary
The ternary positive electrode material is prone to react with the electrolyte in lithium-ion batteries, resulting in excessive deposition of interface by-products, affecting the stability and safety of the battery.
By coating Bi2SeO5 on the ternary material LiNixM1-xO2, a core and shell structure is formed to prevent contact between the ternary material and the electrolyte, and the electrolyte decomposition and interface side reactions under high voltage are suppressed.
It effectively improves the surface structural stability of the positive electrode active material, reduces the dissolution of the surface ions of the ternary material, enhances the stability and safety of the battery, and improves the rate performance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, and a lithium ion battery. Background Art
[0002] In the development of lithium-ion batteries, the selection of positive electrode materials plays a vital role in battery performance. Ternary materials (usually referring to composite oxides containing nickel, cobalt and manganese) are considered to be one of the most promising positive electrode materials due to their high energy density, low cost and excellent electrochemical performance. However, the interface of lithium-ion batteries using ternary materials is easily corroded by the electrolyte and fails. This corrosion is mainly due to the active metal Ni in the high-nickel ternary positive electrode material. 4+ Harmful side reactions with carbonate electrolytes lead to excessive deposition of byproducts at the cathode-electrolyte interface (CEI), which may cause thermal runaway, thus affecting the stability and safety of the battery. In addition, the interaction between traditional carbonate electrolytes and ternary materials causes the surface of the materials to dissolve, resulting in loss of active substances. Summary of the invention
[0003] The embodiments of the present invention provide a positive electrode material and a preparation method thereof, a positive electrode plate, and a lithium-ion battery to solve the problem that the ternary positive electrode material is easy to react and corrode, thereby achieving the effect of improving the stability and safety of the battery.
[0004] Specifically, the present invention provides a positive electrode material, including a core body and a shell coated on the core body, wherein the core body includes LiNi x M 1-x O 2 ; wherein M is selected from at least two elements of Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ce, W, Zr, Ca and P, 0.3≤x<1; the material of the shell is Bi 2 SeO 5 .
[0005] Optionally, the shell has a thickness of 1 nm to 50 nm; And / or, the core body and the shell are doped at adjacent interfaces to form an intermediate layer, and the thickness of the intermediate layer is 0.5 nm to 200 nm.
[0006] Optionally, the Bi 2 SeO 5 The mass proportion in the positive electrode material is 0.05%~5%.
[0007] Optionally, the Bi 2 SeO 5 The mass proportion in the positive electrode material is 0.1%~2%.
[0008] Optionally, the Bi 2 SeO 5 The median particle size D 50 is 1nm~5μm; and the Bi 2 SeO 5 The median particle size D 50 Smaller than the LiNi x M 1-x O 2 The median particle size D 50 .
[0009] Optionally, the Bi 2 SeO 5 The median particle size D 50 It is 10nm~500nm.
[0010] The present invention also provides a method for preparing a positive electrode material, comprising the following steps: LiNi x M 1-x O 2 Materials and Bi(NO 3 ) 3 The material and selenium powder are mixed to obtain a mixed substance; The mixed material is sintered under preset conditions to obtain the positive electrode material.
[0011] Optionally, the preset conditions include: the sintering is carried out in an atmosphere of oxygen or air; the sintering temperature is 300° C. to 700° C.; and the sintering time is 3 h to 10 h.
[0012] The present invention also provides a positive electrode plate, comprising a current collector and an active layer, wherein the active layer is arranged on at least one side of the current collector, and the active layer comprises the positive electrode material as described in any one of the above items.
[0013] The present invention also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.
[0014] The beneficial effects of the present invention are: The present invention adopts Bi 2 SeO 5 Coated in ternary material LiNi x M 1-x O 2 It can effectively prevent the contact between the ternary material and the electrolyte, inhibit the decomposition of the electrolyte under high voltage and the occurrence of interface side reactions, reduce the dissolution and precipitation of ions on the surface of the ternary material, and improve the stability of the surface structure of the positive electrode active material. 2 SeO 5It can provide more effective electric field distribution regulation during battery charging and discharging, reduce the polarization loss of electrode materials, and improve the rate performance of positive electrode active materials. DETAILED DESCRIPTION
[0015] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0016] The embodiment of the present invention provides a positive electrode material, including a core body and a shell coated on the core body, wherein the core body includes LiNi containing lithium element, M element and nickel element. x M 1-x O 2 ; wherein M is selected from at least two elements of Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ce, W, Zr, Ca and P, 0.3≤x<1; the material of the shell is Bi 2 SeO 5 .
[0017] In the embodiment of the present invention, by 2 SeO 5 Coated in ternary material LiNi x M 1-x O 2 It can effectively prevent the contact between the ternary material and the electrolyte, inhibit the decomposition of the electrolyte under high voltage and the occurrence of interface side reactions, reduce the dissolution and precipitation of ions on the surface of the ternary material, and improve the stability of the surface structure of the positive electrode active material. 2 SeO 5 The material can provide more effective regulation of electric field distribution during battery charging and discharging, reduce polarization loss of electrode materials, and improve the rate performance of positive electrode active materials.
[0018] In one embodiment of the present invention, the thickness of the shell is 1nm~50nm. If the thickness of the shell is too large, the LiNi x M 1-x O 2The proportion of the material in the positive electrode material is reduced, which reduces the energy density of the battery; if the thickness of the shell is too small, the shell is thin and easy to break, and it is difficult to effectively prevent the contact between the ternary material and the electrolyte. The thickness of the shell can be 1nm, 3nm, 9nm, 15nm, 20nm, 25nm, 30nm, 40nm or 50nm. Preferably, the thickness of the shell is 3nm~30nm; more preferably, the thickness of the shell can also be 3nm~20nm. The diameter of the core body is 2μm~20μm. If the diameter of the core body is too large, it is not conducive to the preparation of the positive electrode sheet in the later stage; if the diameter of the core body is too small, the Bi coated 2 SeO 5 After the material, the proportion of the core is relatively small, resulting in a decrease in the energy density of the battery.
[0019] In one embodiment of the present invention, the Bi 2 SeO 5 The mass proportion of Bi in the positive electrode material is 0.05% to 5%. 2 SeO 5 The mass percentage of Bi in the positive electrode material is 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. 2 SeO 5 A structurally stable coating is formed on the surface of the ternary material without affecting the Bi 2 SeO 5 The dielectric properties of Bi will not affect the activity of the ternary material, so that the active material obtains excellent electrochemical performance. 2 SeO 5 The mass proportion of the material in the positive electrode material is 0.1%~2%.
[0020] The present invention also provides a method for preparing a positive electrode material, which is used to prepare the positive electrode material in any of the above embodiments, and the preparation method comprises the following steps: LiNi x M 1-x O 2 With Bi(NO 3 ) 3 , and selenium powder to obtain a mixed substance; The mixed material is sintered under preset conditions to obtain the positive electrode material.
[0021] The process steps of this embodiment are simple and can quickly produce Bi 2 SeO 5The coated positive electrode material improves the comprehensive performance of the positive electrode material while maintaining the surface structural stability of the positive electrode material, so that when the positive electrode material is applied to a lithium-ion battery, the lithium-ion battery has excellent electrochemical performance.
[0022] In one embodiment of the present invention, LiNi x M 1-x O 2 The median particle size D 50 2μm~20μm; Bi(NO 3 ) 3 The median particle size D 50 1nm~5μm, and must meet the requirements of LiNi x M 1-x O 2 The median particle size D 50 Greater than Bi(NO 3 ) 3 The median particle size of the generated Bi 2 SeO 5 The median particle size D 50 Also smaller than LiNi x M 1-x O 2 The median particle size D 50 , so that Bi 2 SeO 5 Form a uniform and dense shell, and wrap the ternary material of the core more completely. 2 SeO 5 The particle size is smaller than that of the ternary material LiNi x M 1-x O 2 The particle size makes the small particles of Bi 2 SeO 5 It can disperse the large particles of ternary materials more evenly, increase the contact area between the two, and then make Bi 2 SeO 5 It can be more completely coated on the ternary material.
[0023] Preferably, LiNi x M 1-x O 2 The median particle size D 50 2μm~15μm, Bi 2 SeO 5 The median particle size D 50 More preferably, LiNi x M 1-x O 2 The median particle size D 50 5μm~10μm, Bi 2 SeO5 The median particle size D 50 It is 10nm~500nm.
[0024] In one embodiment of the present invention, the preset conditions include: the sintering is performed in an atmosphere of oxygen or air, and Bi 2 SeO 5 The precursor Bi(NO 3 ) 3 The material and selenium powder form Bi during the sintering process. 2 SeO 5 ,Bi 2 SeO 5 During the sintering process, the contact surface of the two materials forms a transition mixture, which can then form a core and shell distributed from the inside to the outside. If the sintering temperature is too low or the sintering time is too short, it is difficult to form a structure in which the shell tightly wraps around the core; if the sintering temperature is too high or the sintering time is too long, the ternary material particles will grow again, the particle size will increase, and it is easy to cause more serious cation mixing in the crystal structure, thereby deteriorating the electrical performance of the positive electrode material.
[0025] Specifically, the sintering temperature is 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C; and the sintering time is 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h.
[0026] One embodiment of the present application further provides a positive electrode sheet, the positive electrode sheet comprising a current collector and an active layer disposed on at least one side. The active layer comprises the positive electrode material of any of the above embodiments. The current collector may be a conventional metal foil or a composite current collector.
[0027] Specifically, the positive electrode material may also include materials such as a conductive agent, a binder, and a solvent, which may be selected according to relevant technologies and are not limited thereto. In addition, the positive electrode sheet of the present application may be prepared according to relevant technologies. For example, the positive electrode active material, conductive agent, binder, etc. in the above-mentioned positive electrode material are mixed uniformly according to a preset mass ratio, and after grinding to form a slurry with an appropriate amount of solvent, the slurry is coated on the current collector, and the positive electrode sheet is obtained through drying, cutting, and other processes.
[0028] One embodiment of the present application also provides a lithium-ion battery, which includes a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte according to any of the above embodiments. The positive electrode sheet, the separator and the negative electrode sheet can be made into an electrode assembly by a winding process or a lamination process. The electrolyte can be selected from any electrolyte suitable for ternary lithium batteries in the prior art, and is not particularly limited here.
[0029] An embodiment of the present application also provides an electronic device, which includes the above-mentioned lithium-ion battery. The lithium-ion battery serves as a power source for the electronic device and can also be used as an energy storage unit for the electronic device. The electronic device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0030] The present invention is further described below by way of examples.
[0031] Example 1 (1) According to the molar ratio of Bi:Se 2:1, weigh Bi 2 SeO 5 The precursor Bi(NO 3 ) 3 and selenium powder, and Bi(NO 3 ) 3 and selenium powder are added into a planetary ball mill and ball-milled to obtain a first mixture.
[0032] (2) According to Bi 2 SeO 5 and LiNi 0.8 Co 0.1 Mn 0.1 O 2 The theoretical mass ratio is 0.2:99.8, and the first mixture and the median particle size D are weighed respectively. 50 The ternary material LiNi is 9.3μm 0.8 Co 0.1 Mn 0.1 O 2 and mix the two uniformly to obtain a second mixture.
[0033] (3) After sintering the first mixture at 500°C for 10 hours in an oxygen atmosphere, the sintered material is sieved to remove impurities generated by the sagger and other equipment used for sintering, thereby obtaining Bi 2 SeO 5 Positive electrode material with a content of 0.2wt%.
[0034] (4) The positive electrode material, the conductive agent CNT (carbon nanotube) and the binder PVDF (polyvinylidene fluoride) are fully stirred and mixed in N-methylpyrrolidone solvent at a mass ratio of 97:1.5:1.5 to form a uniform positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil. After drying and cold pressing, the positive electrode sheet is obtained.
[0035] (5) Preparation of negative electrode sheet The negative electrode active material silicon oxygen-carbon composite material, the conductive agent acetylene black, the binder styrene butadiene rubber and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 95:2:2:1 to form a uniform negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector copper foil. After drying and cold pressing, the negative electrode sheet is obtained.
[0036] (6) Preparation of lithium-ion batteries The isolation membrane in this step is a PE porous polymer film, and the electrolyte is a carbonate electrolyte.
[0037] The positive electrode sheet, the separator film, and the negative electrode sheet prepared in step (5) are stacked in sequence, so that the separator film is located between the positive and negative electrode sheets for isolation. The stacked positive electrode sheet, the separator film, and the negative electrode sheet are wound into a winding core. The winding core is placed in the aluminum-plastic film bag formed by the punching and injected with electrolyte. After vacuum packaging, standing, formation and other processes, a lithium-ion battery is obtained.
[0038] The differences between Example 2 to Example 13 and Example 1 are shown in Table 1: Table 1 Parameter comparison table Comparative Example 1 The difference between this comparative example and Example 1 is that the median particle size D 50 The ternary material LiNi is 9.3μm 0.8 Co 0.1 Mn 0.1 O 2 , sintered at 500 ° C for 10 h in an oxygen atmosphere, and the sintered material was sieved to obtain uncoated LiNi 0.8 Co 0.1 Mn 0.1 O 2 Positive electrode material and used in the preparation of lithium-ion batteries.
[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that the median particle size D 50 The ternary material LiNi is 4.9μm 0.8 Co 0.1 Mn 0.1 O 2 , sintered at 500 ° C for 10 h in an oxygen atmosphere, and the sintered material was sieved to obtain uncoated LiNi 0.8 Co 0.1 Mn 0.1 O 2 Positive electrode material and used in the preparation of lithium-ion batteries.
[0040] Comparative Example 3 The difference between this comparative example and Example 1 is that the median particle size D 50 The ternary material LiNi is 6.5μm 0.6 Co 0.1 Mn 0.3 O 2 , sintered at 500 ° C for 8 h in an oxygen atmosphere, and the sintered material was sieved to obtain uncoated LiNi 0.8 Co 0.1 Mn 0.1 O 2 Positive electrode material and used in the preparation of lithium-ion batteries.
[0041] The lithium-ion batteries of the above embodiments and comparative examples were tested: 1) High temperature cycle performance test The lithium-ion batteries of the above embodiment and comparative example were charged to 4.3V at 45°C at 0.8C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current. The first-cycle reversible capacity and first-cycle coulomb efficiency of the battery were calculated.
[0042] The charge and discharge were cycled in the above manner. After 500 cycles of charge and discharge, the capacity retention rate of the battery at the 500th cycle was calculated. The corresponding test results of each lithium-ion battery are shown in Table 2.
[0043] 2) Ratio test The lithium-ion batteries of the above-mentioned embodiment and comparative example were charged at 0.5 times and discharged at 0.5C for 10 cycles (0.5C / 0.5C) at 25°C; then charged at 0.5C and discharged at 1C for 10 cycles (0.5C / 1C); and finally charged at 0.5C and discharged at 3C for 10 cycles (0.5C / 3C). The test results are shown in Table 2.
[0044] Table 2 Performance test table It can be seen from Table 2 that compared with Comparative Example 1, Example 1 uses the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O 2 Add a small amount of Bi 2 SeO 5 , so that after sintering, a structurally stable coating layer is formed on the surface of the ternary material to prevent the contact between the ternary material and the electrolyte, inhibit the decomposition of the electrolyte under high voltage and the occurrence of interface side reactions, reduce the dissolution and precipitation of ions on the surface of the ternary material, and improve the stability of the surface structure of the positive electrode active material. In addition, Bi with a high dielectric constant 2 SeO 5It can provide more effective electric field distribution control during battery charging and discharging, reduce polarization loss of electrode materials, and improve rate performance of positive electrode active materials. Therefore, the high temperature cycle performance and discharge rate of the lithium ion battery prepared in Example 1 are better than those in Comparative Example 1. Similarly, compared with Comparative Example 2, Example 2 only has a ternary material LiNi 0.8 Co 0.1 Mn 0.1 O 2 Add Bi 2 SeO 5 Similarly, the high temperature cycle performance and discharge rate of the lithium ion battery prepared in Example 2 are better than those in Comparative Example 2.
[0045] Compared with Example 1, Examples 2 to 4 change the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O 2 The median particle size D 50 ; With the LiNi 0.8 Co 0.1 Mn 0.1 O 2 The median particle size D 50 With the increase of the first-week reversible capacity, the first-week coulomb efficiency and the discharge rate of each lithium-ion battery gradually decreased, while the capacity retention rate after 500 cycles increased. The reason may be that when the particles of the ternary material increase, their specific surface area decreases, and the diffusion path of lithium ions in the electrode material becomes longer, thereby reducing the diffusion rate of lithium ions and causing more lithium ions to be unable to be embedded in the positive electrode material in time, thus causing the battery's charging efficiency and capacity to decrease. In addition, during high-rate discharge, the capacity will drop rapidly and the coulomb efficiency will also decrease. However, a larger particle size can reduce the volume change of the ternary material during the cycle, reduce stress concentration, and thus improve the cycle stability, that is, improve the capacity retention rate after 500 cycles.
[0046] Compared with Example 1, Examples 5 to 9 change Bi 2 SeO 5 The amount of Bi 2 SeO 5 With the increase of the addition amount of Bi, the first-week reversible capacity, first-week coulomb efficiency and discharge times of lithium-ion batteries first increased and then decreased, while the capacity retention rate after 500 cycles continued to increase. The reason may be: 2 SeO 5 When the amount of Bi added is small, a sufficiently thick and stable coating layer cannot be formed, so it is difficult to prevent the contact between the ternary material and the electrolyte, and the decomposition of the electrolyte under high voltage and the inhibition of interface side reactions are weak; 2 SeO 5As the amount of Bi increases, the thickness of the coating layer formed after sintering gradually increases, which can effectively inhibit the decomposition of the electrolyte under high voltage and the occurrence of interface side reactions, and improve the high temperature cycle performance and discharge rate of lithium-ion batteries. 2 SeO 5 When the amount of addition continues to increase, the coating layer formed after sintering is too thick, which causes the diffusion path of lithium ions in the electrode material to become longer, thereby reducing the diffusion rate of lithium ions and causing more lithium ions to be unable to be embedded in the positive electrode material in time, thus affecting the battery's charging efficiency, capacity and coulombic efficiency. As the thickness of the coating layer increases, the inhibitory effect on the volume change of the ternary material during the cycle increases, thereby reducing stress concentration and improving cycle stability, that is, improving the capacity retention rate after 500 cycles.
[0047] Example 10 Compared with Example 1, the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O 2 Replaced with LiNi 0.6 Co 0.1 Mn 0.3 O 2 , the nickel content is reduced, so the energy density is reduced, while with lower nickel content, its structure is relatively stable, so it may show better cycle stability during the cycle process.
[0048] Compared with Example 10, Example 11 and Example 13, the LiNi 0.6 Co 0.1 Mn 0.3 O 2 Median particle size D 50 , resulting in an increase in the first-week reversible capacity, first-week coulomb efficiency and discharge rate of the lithium-ion battery in Example 11 and Example 13, while a decrease in the capacity retention rate after 500 cycles. The reason may be that when the ternary material particles are reduced, their specific surface area increases, and the diffusion path of lithium ions in the electrode material becomes shorter, which increases the diffusion rate of lithium ions, so that more lithium ions can be embedded in the positive electrode material in time, thus increasing the charging efficiency and capacity of the battery. However, a smaller particle size is not conducive to reducing the volume change of the ternary material during the cycle, and cannot reduce the stress concentration effect, so the cycle stability is poor, that is, the capacity retention rate after 500 cycles is reduced.
[0049] Compared with Example 10, Example 12 and Example 13 compared with Example 11 shortened the sintering time, which is not conducive to the uniform molding of the ternary material and the coating layer. Therefore, the various performances of the lithium-ion batteries in Examples 12 and 13 are reduced.
[0050] Example 13 Compared with Comparative Example 3, by using the ternary material LiNi 0.6 Co 0.1 Mn 0.3 O 2 Add a small amount of Bi 2 SeO 5 , so that after sintering, a structurally stable coating layer is formed on the surface of the ternary material to prevent the contact between the ternary material and the electrolyte, thereby inhibiting the decomposition of the electrolyte under high voltage and the occurrence of interface side reactions, reducing the dissolution and precipitation of ions on the surface of the ternary material, and improving the stability of the surface structure of the positive electrode active material. In addition, Bi with a high dielectric constant 2 SeO 5 It can provide more effective electric field distribution control during battery charging and discharging, reduce polarization loss of electrode materials, and improve rate performance of positive electrode active materials. Therefore, the high temperature cycle performance and discharge rate of the lithium ion battery prepared in Example 13 are better than those in Comparative Example 3.
[0051] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: It includes a core body and a shell coated on the core body, wherein the core body includes LiNi x M 1-x O2; wherein M is selected from at least two elements of Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ce, W, Zr, Ca and P, and 0.3≤x<1; the material of the shell is Bi2SeO5.
2. The positive electrode material according to claim 1, characterized in that The shell has a thickness of 1 nm to 50 nm; And / or, the core body and the shell are doped at adjacent interfaces to form an intermediate layer, and the thickness of the intermediate layer is 0.5 nm to 200 nm.
3. The positive electrode material according to claim 2, characterized in that The LiNi x M 1-x The median particle size D of O2 50 2μm~20μm.
4. The positive electrode material according to claim 1, characterized in that The mass proportion of Bi2SeO5 in the positive electrode material is 0.05%~5%.
5. The positive electrode material according to claim 4, characterized in that The mass proportion of Bi2SeO5 in the positive electrode material is 0.1%~2%.
6. The positive electrode material according to claim 1, characterized in that The median particle size D of the Bi2SeO5 50 1nm~5μm; and the median particle size D of the Bi2SeO5 50 Smaller than the LiNi x M 1- x The median particle size D of O2 material 50 .
7. The positive electrode material according to claim 6, characterized in that The median particle size D of the Bi2SeO5 50 It is 10nm~500nm.
8. A method for preparing a positive electrode material according to any one of claims 1 to 7, characterized in that: The following steps are involved: LiNi x M 1-x O2 material is mixed with Bi(NO3)3 material and selenium powder to obtain a mixed substance; The mixed material is sintered to obtain the positive electrode material.
9. A positive electrode sheet, characterized in that: The invention comprises a current collector and an active layer, wherein the active layer is arranged on at least one side of the current collector, and the active layer comprises the positive electrode material according to any one of claims 1 to 7.
10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Lithium-rich manganese-based cathode material and preparation method thereof and lithium ion battery
CN111640936A
SeS2-coated high-nickel ternary positive electrode material and preparation method thereof
CN113488631A
Positive electrode active material and preparation method thereof, positive electrode plate and lithium ion battery
CN117525411A
Modified positive electrode material, preparation method thereof and all-solid-state lithium ion battery
CN118039833A
Pre-lithiated silicon-carbon negative electrode material, preparation method and application
CN118825229A